Dependence of mesomorphism on molecular rigidity of nonlinear and linear isomeric and nonisomeric chalconyl esters. (2nd July 2016) - Jain, B. B.; Patel, R. B.
ABSTRACT: The novel thermotropic liquid crystalline (LC) materials have been synthesized and studied through chalconyl ester nonlinear (meta substituted) homologous series RO-C6 H4 ‒CH˭CH‒COO‒C6 H4 -CO‒CH˭CH‒C6 H4 -OC14 H29 (n) with a view to understand the effect of molecular structure on LC behavior with reference to determine the difference between linear and nonlinear shaped molecules. Novel series consisted of thirteen members, whose nematogenic enantiotropic mesomorphism commences from C6 homologue and continued up to C18 homologue with the absence of smectogenic character. C1 to C5 homologues are nonliquid crystals as determined through an optical polarising microscope (POM) equipped with a heating stage. Transition temperatures of LC homologues alternate and are lower than the corresponding n-alkoxy cinnamic acids. Cr-N/I and N-I transition curve behaved in normal manner. N-I transition curve exhibited odd-even effect in a phase diagram. Textures of nematic phase are threaded or Schlieren or determined by miscibility method and from observing mesophase on the top of the POM. Thermal stability for nematic is 92.5 and mesophase length minimum to maximum is 19.0 to 32.0°C at the C10/18 and C6 homologue. Group efficiency order on the basis of thermal stability is Thus, novel series is nematogenic and low melting type. Analytical and spectral data confirmed the molecular structures of homologues.